An Imagist Reading of William Carlos Williams’ “The Wanderer” - Essa, Zahraa (Al-Adab Journal, 2024)
This paper examines William Carlos Williams’ “The Wanderer,” one of the earliest poems in his poetic career, in terms of one of the Imagistic tenets that Williams adopted, that is “Direct treatment of the ‘thing’, whether subjective or objective.” Although Williams was highly influenced by Keatsian idealism which appeared in his early works, yet “The Wanderer” presents his attempt of making this romantic ideology as a starting point for his more imagistic approach. The paper follows and investigates the journey of the poet (in the poem) in his flight from the heights of his past romantic wanderings into more local and modernist encounters which he presents as episodes and images. The culmination of this experience leads to a baptism ritual through which the poet announces a new wandering that is would be purely imagist.